"Geniusz, ten możny pan, gustu jest hołdownikiem". Wokół polskiej prapremiery "Hamleta" - Kurek, Krzysztof (Wydawnictwo "Poznańskie Studia Polonistyczne", Poznań, 1999)
The first chapter, entitled "On Polish First-Night Performance of Hamlet", is devoted to the first Polish staging of the tragedy. The first-night performance was staged on April 9th 1798 at the Lwów theatre, which at that time was directed by Wojciech Bogusławski. The author presents the most important historical context surrounding the production of the play and reminds of the concurrent presence of German-language productions of Shakespeare's plays in Warsaw prior to 1794. After a detailed description of individual versions of Schroeder's adaptations of "Hamlet", the autor analyses the text of the Bogusławski translation of the tragedy and the accompanying text of "Uwagi nad Hamletem" ("Notes on Hamlet").
Keywords: Reception of William Shakespeare's "Hamlet" in Poland in the first half of the nineteenth century; William Shakespeare; Wojciech Bogusławski; Klasycyzm wobec twórczości Szekspira